SAT0115 Effect of biological disease modifying anti-rheumatic drugs (BDMARDS) on cardio vascular disease (CVD) risk in ra patients:three years results from a canadian cohort. (15th June 2017) - Khraishi, M; Molta, C; Lewis, A
Abstract : Background: RA patients have a higher risk for developing CV Diseases (e.g. IHD and stroke) than the general population.We reported previously (ACR, EULAR) the results CV risk in our patients treated with bDMARDs for 1& 2 years. Objectives: To assess the effect of bDMARDs treatment on 10-year CV disease risk in patients with RA after 36 months and evaluate the impact of their use on the incidence of CV events Methods: A cohort of RA patients was followed prospectively.Demographics, disease activity parameters, inflammatory markers, CV events, CVD 10 year risk assessment [Framingham Risk Score (FRS)] were ascertained at the baseline and every six months, up to 36 months.Statistical analysis utilized SPSS (IBM version 24) software. Results: 321 patients were included, of those 270 patients were followed for three years. Eight BDMARDs were included evaluating their effect on disease activity and CV risk in 233 patients who continued on their prospective biologic for the three years. Significant overall reduction in disease activity in all groups was obtained as compared to baseline. The whole group DAS improved from 3.996 to 3.118. The HAQ also improved significantly (1.201 to 0.857) and the CRP improved significantly (12.91 mg/L to 7.3). Overall, Total cholesterol (TC) changed from 5.195 mmol/L at baseline to 4.992 (P 0.001). High Density Lipoprotein Cholesterol (HDL-C) increased significantly at 36 months from 1.336 to 1.376. However, the Atherogenic Index (AI) for the whole cohort changed from 3.636 to 3.845. The overall 10 year risk of cardiovascular event increased from 12.878 to 13.8 The cohort included 321 patients. Eight bDMARDs were evaluated to assess their effect on disease activity and CVD risk. The outcomes in 233 patients who continued their prospective biologic for the three years were reported (table). 77% were females, median RA duration was 11 ys. Significant reduction in disease activity in all groups was achieved vs. baseline. The DAS improved from 3.996 to 3.118, the HAQ improved significantly (1.201 to 0.857) and the CRP also improved significantly (12.91 mg/L to7.3). Overall, Total cholesterol (TC) changed from 5.195 mmol/L at baseline to 4.992 (P 0.001). High Density Lipoprotein Cholesterol (HDL-C) increased significantly at 36 months from 1.336 to 1.376. The Atherogenic Index (AI) for the cohort changed from 3.636 to 3.845. The overall 10 year risk of cardiovascular event increased from12.878 to 13.8. Conclusions: The bDMARDS studied were effective in controlling the disease activity of RA. Although the overall CVD risk was not reduced in the group as a whole at 36 months, bDMARDS may still play a role in reducing the CVD risk in these patients Disclosure of Interest: M. Khraishi Grant/research support from: Roche Canada, C. Molta: None declared, A. Lewis: None declared